Analysis of the Use of Cobweb-Shaped Foundation for Road Pavement Construction - Soelarso Soelarso; Rindu Twidi Bethary (JURUSAN TEKNIK SIPIL, 2023)
Flexible pavement and rigid pavement are the two types of road construction pavement. This study attempts to employ CobwebShaped Foundation (KSLL) as an alternative style of road construction, KSLL being the labor of the nation's youth and commonly used in structures. PT. Katama Suryabumi owns the building patent. This study attempts to incorporate KSLL, which has been widely utilized for building foundations, into road construction. The study was carried out by doing experimental comparisons and analysis using the Finite Element Method, in which the model is summarized in order to achieve accurate comparison findings, and it is believed that they will find a formula connected to the design of KSLL for road building. It is expected that this concept may be used to solve problems in designs that do not currently have regulations or standards. As a result, the study objectives are as follows: a) The KSLL foundation is a stiff pavement that may be used as an alternative pavement. b) Calculating the KSLL foundation's strength and settling. b) Restoring and improving the KSLL foundation